The tendon interfascicular basement membrane provides a vascular niche for CD146+ cell subpopulations - Marr, Neil; Zamboulis, Danae E.; Werling, Dirk; Felder, Alessandro A.; Dudhia, Jayesh; Pitsillides, Andrew A.; Thorpe, Chavaunne T. (Frontiers in Cell and Developmental Biology, 2023)
The interfascicular matrix (IFM; also known as the endotenon) is critical to the mechanical adaptations and response to load in energy-storing tendons, such as the human Achilles and equine superficial digital flexor tendon (SDFT). We hypothesized that the IFM is a tendon progenitor cell niche housing an exclusive cell subpopulation. Immunolabelling of equine SDFT was used to identify the IFM niche, localising expression patterns of CD31 (endothelial cells), Desmin (smooth muscle cells and pericytes), CD146 (IFM cells) and LAMA4 (IFM basement membrane marker). Magnetic-activated cell sorting was employed to isolate and compare in vitro properties of CD146+ and CD146- subpopulations. Labelled for CD146 using standard histological and 3D imaging of large intact 3D segments revealed an exclusive interfascicular cell subpopulation that resides in proximity to a basal lamina which forms extensive, interconnected vascular networks. Isolated CD146+ cells exhibited limited mineralisation (osteogenesis) and lipid production (adipogenesis). This study demonstrates that the IFM is a unique tendon cell niche, containing a vascular-rich network of basement membrane, CD31+ endothelial cells, Desmin+ mural cells, and CD146+ cell populations that are likely essential to tendon structure and/or function. Contrary to our hypothesis, interfascicular CD146+ subpopulations did not exhibit stem cell-like phenotypes. Instead, our results indicate CD146 as a pan-vascular marker within the tendon IFM. Together with previous work demonstrating that endogenous tendon CD146+ cells migrate to sites of injury, our data suggest that their mobilisation to promote intrinsic repair involves changes in their relationships with local IFM vascular and basement membrane constituents.